Menelisik Fenomena Learning Loss dalam Konteks Pendidikan Tinggi di Provinsi Lampung - Hadiati, Eti; Kamil, Badrul; Dwiyanto, Agus; Setianingrum, Diah Ayu (Instructional Development Journal, 2024)
The COVID-19 pandemic that has hit Indonesia since March 2020 has had a significant impact on various sectors of life, including education. Since the pandemic emergency, the government has launched online learning to reduce virus transmission. However, the implementation of online learning has encountered various obstacles such as uneven internet access, varying parental abilities in supporting learning, and student boredom. In the 2022/2023 academic year, the government will begin to return to face-to-face learning (PTM) while still implementing strict health protocols. However, there are concerns regarding the phenomenon of learning loss, namely the decline in students' knowledge and skills due to prolonged online learning. This phenomenon is very important to study, especially in higher education, considering its impact on students' readiness to face the world of work and the next level of education. This research aims to examine the phenomenon of learning loss among students at several universities in Lampung Province.